Analisis Penerapan Total Productive Maintenance (TPM) Menggunakan Overall Equipment Efectiveness (OEE) Dan Six Big Losses Pada Mesin Cold Leveller PT. KPS - Muhamad Bob Anthony (Industrial Engineering, Engineering of Faculty, Universitas Kadiri, 2019)
PT. KPS is one steel company in Indonesia that produces steel products in the form of slab and plate that is marketed in the country up to foreign countries. Cold leveller machine is a machine that serves to flatten the surface of the plate. Problems occurred in the machinery that is often experienced a breakdown so that the plate with uneven surfaces more and more because of the time machine working on the wane. This research aims to quantify the value of the overall equipment effectiveness (OEE), calculating the factor of six big losses and figure out the root cause of the problem, the dominant factor of the six big losses with the fishbone diagram. The OEE value obtained on the engine cold leveller is 82%. The biggest factor that causes the low effectiveness of the machine that is the reduced speed losses amounting to 11.59% and equipment failure losses amounted to 6.04%. The proposed corrective actions is prioritizing the main TPM pillar 3 that is autonomous maintenance, quality maintenance, training and education.PT. KPS adalah salah satu perusahaan baja di Indonesia yang memproduksi produk baja berupa slab dan plate yang dipasarkan di dalam negeri hingga ke luar negeri. Mesin cold leveller merupakan mesin yang berfungsi meratakan permukaan plate yang tidak rata. Permasalahan yang terjadi pada mesin tersebut yaitu sering mengalami breakdown sehingga plate dengan permukaan yang tidak rata semakin banyak karena waktu bekerja mesin semakin berkurang. Penelitian ini bertujuan untuk menghitung nilai overall equipment effectiveness (OEE), menghitung nilai faktor six big losses dan mengetahui akar penyebab masalah yang dominan dari faktor six big losses dengan fishbone diagram. Nilai OEE yang didapat pada mesin cold leveller adalah sebesar 82%. Faktor terbesar yang menyebabkan rendahnya efektifitas mesin yaitu reduced speed losses sebesar 11,59% dan equipment failure losses sebesar 6,04%. Tindakan perbaikan yang diusulkan adalah memprioritaskan 3 pilar utama TPM yaitu autonomous maintenance, quality maintenance, training dan education.